Paradigma Simbiosis Nilai dan Eudaimonia Kepuasan Kerja dalam Transformasi Perilaku Organisasi Pendidikan Islam di Institut Agama Islam Hidayatullah Batam - Nurazizah Alamsyah; Rahmat Hidayat; Sismawati Sismawati; Jamrizal Jamrizal; Samsu Samsu (Moral : Jurnal kajian Pendidikan Islam, 2025)
The research results show that there is a significant relationship between the value symbiosis paradigm and job satisfaction eudaimonia on organizational behavior. Well-implemented Islamic values ​​support eudaimonic job satisfaction, which in turn increases the transformation of more positive organizational behavior. Faculty and staff who feel there is alignment between their work and their values ​​tend to work better and demonstrate behavior that supports organizational goals.